Implementation of the Qiroati Method in Improving Quran Literacy at SDIT al Madinah Karawang - Farah Fauziah Noor; Lilis Karyawati; Nia Karnia (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The Qiroati method is a method of learning to read the Koran which directly practices tart reading in accordance with the qoidah of practical recitation. One of the obstacles in the process of learning to read the Koran in general is that the teacher does not use the method, only reads normally. Therefore there are still some students who are not fluent in reading the Koran because they feel the method used is less effective, unstructured and seems monotonous and makes students feel bored in the process of learning to read and write the Koran. This research is intended to find out how the application of the Qiroati method through BTQ learning improves the ability to read the Koran in students at SDIT Al Madinah Karawang. This type of research is field research. In this study, the researcher will describe the application of the Qiroati method through BTQ learning in improving the ability to read the Koran. While the nature of the research is descriptive in nature. Data collection techniques used are interviews, tests and documentation. For data analysis techniques used are data collection, presentation and conclusion. The results of research conducted by researchers can be concluded that the Qiroati method can improve students' Al-Quran reading skills with evidence that students get good grades when reading the Al-Quran test. The implementation of the Qiroati method is by the way the teacher exemplifies correct reading which then students read together. So that with the Qiroati method students can find out how to read correctly.